2014
DOI: 10.2217/pgs.14.119
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study Identifies CAMKID Variants Involved in Blood Pressure Response to Losartan: The Sophia Study

Abstract: Using a genome-wide approach, we identified the CAMK1D gene as a novel locus associated with blood pressure response to losartan. CAMK1D gene characterization may represent a useful tool to personalize the treatment of essential hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…changes in diet, exercise, time-of-day, combinations of prescribed drugs, alcohol usage, etc .). Several PGx GWAS have reported variants in plausible genes associated with thiazide diuretics (Chittani et al, 2015; Turner et al, 2008; Turner et al, 2013), angiotensin II receptor blockers (Frau et al, 2014; Turner et al, 2012), and beta-blockers (Gong et al, 2015; Gong et al, 2016); yet, most of these studies involve relatively small discovery sample-sizes and are underpowered, as far as detecting associations having genome-wide significance ( i.e. P < 5 × 10 −8 ).…”
Section: Genetic Studies Of Pgx Traitsmentioning
confidence: 99%
“…changes in diet, exercise, time-of-day, combinations of prescribed drugs, alcohol usage, etc .). Several PGx GWAS have reported variants in plausible genes associated with thiazide diuretics (Chittani et al, 2015; Turner et al, 2008; Turner et al, 2013), angiotensin II receptor blockers (Frau et al, 2014; Turner et al, 2012), and beta-blockers (Gong et al, 2015; Gong et al, 2016); yet, most of these studies involve relatively small discovery sample-sizes and are underpowered, as far as detecting associations having genome-wide significance ( i.e. P < 5 × 10 −8 ).…”
Section: Genetic Studies Of Pgx Traitsmentioning
confidence: 99%
“…Through a whole-genome approach, the authors identified a significant association between 4 SNPs on CAMK1D gene and BP response. CAMK1D encodes for a calcium-dependent kinase that modulates the transcription of factors NURR1, ARF1, ATF2 and CREB, involved in aldosterone production in the adrenal zona glomerulosa [75]. …”
Section: Pharmacogenomicsmentioning
confidence: 99%
“…The biological effect of these genes, as well as previously mentioned genes, can be found in Table 2. As part of the Study of the Pharmacogenomics in Italian hypertensive patients treated with the Angiotensin receptor blocker losartan (SOPHIA), a GWAS on BP response was performed in 372 hypertensives treated with losartan for 4 weeks [43•]. Four SNPs (rs10752271, rs10906202, rs4747995, and rs10737061) in the CAMK1D gene were significantly associated with SBP reduction response to losartan ( P <1×10 −5 ).…”
Section: Pharmacogenetics Of Antihypertensive Responsementioning
confidence: 99%